2014
DOI: 10.1586/14737140.2014.983083
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib and lung cancer

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) have an established role in the treatment of non-small-cell lung cancer (NSCLC). First-generation reversible ATP-competitive EGFR-TKIs are approved for the initial treatment of patients with EGFR mutation-positive advanced NSCLC. Afatinib is an irreversible second-generation EGFR-TKI with potent preclinical activity against EGFR (wild type and mutant), HER2, HER4 and EGFR-mutant NSCLC with acquired resistance to reversible EGFR-TKI. LUX-Lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…EGFR signaling can be constitutively activate through genic mutation or genic amplification or both, which has been shown to be closely related to the occurrence, progression and poor prognosis of NSCLC [ 4 6 ]. Besides, there have studies demonstrated activation mutations in the tyrosine kinase domain of EGFR and this percentage of mutations may range from 15% to 40%, particularly common in Asian, female, never or light smoking NSCLC [ 7 10 ]. More than 90% of the known activating EGFR mutations are deletion of exon 19 (in-frame) and point mutation of exon 21 (L858R) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR signaling can be constitutively activate through genic mutation or genic amplification or both, which has been shown to be closely related to the occurrence, progression and poor prognosis of NSCLC [ 4 6 ]. Besides, there have studies demonstrated activation mutations in the tyrosine kinase domain of EGFR and this percentage of mutations may range from 15% to 40%, particularly common in Asian, female, never or light smoking NSCLC [ 7 10 ]. More than 90% of the known activating EGFR mutations are deletion of exon 19 (in-frame) and point mutation of exon 21 (L858R) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…By irreversible covalent bond, it blocks enzymatic activity of active ErbB receptor family members. Because the irreversible covalent binding can inhibit the kinase activity until the synthesis of new receptors, the action time of afatinib may longer than reversible EGFR TKIs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non‐small cell lung cancer accounts for 80%‐85% of all lung cancers, and represents the leading cause of cancer‐related deaths in men and women worldwide . First‐generation EGFR TKI, gefitinib and erlotinib, and the second‐generation EGFR inhibitor afatinib, used as first‐line treatments for advanced NSCLC patients with EGFR‐activating mutations, have shown promising clinical results with superior progression‐free survival compared with platinum doublet chemotherapy regimens . Third‐generation EGFR inhibitors, such as AZD9291, have been developed with the aim of overcoming resistance induced by the EGFR T790M mutation, which occurs in approximately half of patients on EGFR‐TKI therapy that show disease progression .…”
Section: Introductionmentioning
confidence: 99%
“…Afatinib (Giotrif ® , BoehringerIngelheim): Afatinib is an anilinequinazoline derivative with a reactive acrylamide group which can modify the catalytic domains of EGFR, HER2, and ErbB-4, with orally bioavailable irreversible EGFR inhibitor and afatinibaction may longer than reversible EGFR TKIs [15,27].…”
Section: Second Generation Egfr Tk Inhibitorsmentioning
confidence: 99%